Into the Rhythm: Evaluating Breathing Instruction Sound Experiences on the Run with Novice Female Runners - Vincent van Rheden; Eric Harbour; Thomas Finkenzeller; Alexander Meschtscherjakov (Multimodal Technologies and Interaction, 2024)
Running is a popular sport throughout the world. Breathing strategies like stable breathing and slow breathing can positively influence the runner’s physiological and psychological experiences. Sonic breathing instructions are an established, unobtrusive method used in contexts such as exercise and meditation. We argue sound to be a viable approach for administering breathing strategies whilst running. This paper describes two laboratory studies using within-subject designs that investigated the usage of sonic breathing instructions with novice female runners. The first study (N = 11) examined the effect of information richness of five different breathing instruction sounds on adherence and user experience. The second study (N = 11) explored adherence and user experience of sonically more enriched sounds, and aimed to increase the sonic experience. Results showed that all sounds were effective in stabilizing the breathing rate (study 1 and 2, respectively: mean absolute percentage error = 1.16 ± 1.05% and 1.9 ± 0.11%, percent time attached = 86.81 ± 9.71% and 86.18 ± 11.96%). Information-rich sounds were subjectively more effective compared to information-poor sounds (mean ratings: 7.55 ± 1.86 and 5.36 ± 2.42, respectively). All sounds scored low (mean < 5/10) on intention to use.